Decoding ChatGPT: Basis premier to get insight into conversational artificial intelligence - Faerozh Madli; Yuzainy Janin; Mat Salleh @ Salleh Wahab; Stephen Laison Sondoh Jr.; Suddin Lada; Shaierah Gulabdin; Ag Kaifah Riyard Kiflee; Charlie Albert Lasuin (Semarak Ilmu, 2024)
The contemporary landscape witnesses a rapid evolution in the utilization of Artificial Intelligence (AI), observable across diverse sectors and industries. One of the most widely recognized AI technologies is ChatGPT. Like other AI-based technologies, ChatGPT is extensively used in various applications at both individual and organizational levels. However, what is concerning is the trend of using ChatGPT technology without understanding its fundamentals. Therefore, this study focuses on unravelling the basic knowledge of this highly advanced platform, ChatGPT. The findings of this study are benefiting many parties, especially individuals interested in using this platform. These benefits are not only limited to the community but also contribute to the body of knowledge by providing insights into the fundamental aspects of this platform. The study's positive outcomes will contribute to forming a community layer with a deeper understanding of ChatGPT and improved readiness prior to its utilization.